Development and Evaluation of Lipid Nanoparticles Containing Natural Botanical Oil for Sun Protection: Characterization and in vitro and in vivo Human Skin Permeation and Toxicity - Andréo-Filho, N.; Bim, A.; Kaneko, T.; Kitice, N.; Haridass, I.; Abd, E.; Santos Lopes, P.; Thakur, S.; Parekh, H.; Roberts, M.; Grice, J.; Benson, Heather; et al. (S. Karger AG, 2017)
The use of sunscreen products is widely promoted by schools, government agencies, and health-related organizations to minimize sunburn and skin damage. In this study, we developed stable solid lipid nanoparticles (SLNs) containing the chemical UV filter octyl methoxycinnamate (OMC). In parallel, we produced similar stable SLNs in which 20% of the OMC content was replaced by the botanical urucum oil. When these SLNs were applied to the skin of human volunteers, no changes in fluorescence lifetimes or redox ratios of the endogenous skin fluorophores were seen, suggesting that the formulations did not induce toxic responses in the skin. Ex vivo (skin diffusion) tests showed no significant penetration. In vitro studies showed that when 20% of the OMC was replaced by urucum oil, there was no reduction in skin protection factor (SPF), suggesting that a decrease in the amount of chemical filter may be a viable alternative for an effective sunscreen, in combination with an antioxidant-rich vegetable oil, such as urucum. There is a strong trend towards increasing safety of sun protection products through reduction in the use of chemical UV filters. This work supports this approach by producing formulations with lower concentrations of OMC, while maintaining the SPF. Further investigations of SPF in vivo are needed to assess the suitability of these formulations for human use.